1973
DOI: 10.1002/cjce.5450510111
|View full text |Cite
|
Sign up to set email alerts
|

Wall heat transfer to chemical reactors

Abstract: C R R A N und M . IM. ZRZZARHY' De#mrtmmt of Chemical Engineering, University of Puerto Rim, Mayaguez, P w r t o R k oThe effects of chemical reactions on wall heat transfer coefficients in packed bed reactors operating at equilibrium or near equiliirium conditions are explored by means of onedimensional and two-dimensional models. Both approaches suggest using Damkohler number or ratios of reacting to frozen heat capacity as parametcrs in heat transfer correlations. Available data for the methane-steam reform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1979
1979
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Hofmann and Chao found that under reaction conditions k bed /k g is smaller than without reaction [34,35]. Apparently, there is an interaction between this static thermal conductivity and the kinetics [36].…”
Section: Ft Fixed-bed Reactor Model (Multitubular Reactor)mentioning
confidence: 99%
“…Hofmann and Chao found that under reaction conditions k bed /k g is smaller than without reaction [34,35]. Apparently, there is an interaction between this static thermal conductivity and the kinetics [36].…”
Section: Ft Fixed-bed Reactor Model (Multitubular Reactor)mentioning
confidence: 99%
“…This formulation is called the lumped parameter model in the chemical engineering literature. It has been found that these lumped parameter models often overpredict the temperature of hot spots in the reactors [37,38], which implies that the models underestimate the heat transfer rate at the wall. Some investigators [42][43][44][45][46] have attributed the disparity of the theoretical and experimental results in a wall-cooled catalytic reactor to the assumption of a flat velocity profde (Plug flow) in the lumped parameter model, which does not take into consideration the nonuniform velocity distribution near the wall due to the channeling effects.…”
Section: 2mentioning
confidence: 99%
“…A rational design of this type of reactor is essential in order to avoid disastrous runaway temperature, low conversion rate and catalyst damages [37,38].…”
mentioning
confidence: 99%
“…The heat removal from the reactor had to be increased in the model for fast reaction or high temperature conditions. This interaction between heat transfer and reaction rate is not unusual and has been seen by other workers (Paterson and Carberry, 1983;Hofmann, 1979;Panthel, 1977;Hlavacek and Votruba, 1977;Chao, et al, 1973). Therefore, estimation of both heat transfer parameters and kinetic parameters are necessary under reactive conditions.…”
Section: Experiments Without Reactionmentioning
confidence: 78%